Decreased telomere length in children with cartilage-hair hypoplasia. Issue 5 (16th December 2016) - Kostjukovits, Svetlana; Degerman, Sofie; Pekkinen, Minna; Klemetti, Paula; Landfors, Mattias; Roos, Göran; Taskinen, Mervi; Mäkitie, Outi
Abstract : Background: Cartilage-hair hypoplasia (CHH) is an autosomal recessive chondrodysplasia caused by RMRP (RNA component of mitochondrial RNA processing endoribonuclease) gene mutations. Manifestations include short stature, variable immunodeficiency, anaemia and increased risk of malignancies, all of which have been described also in telomere biology disorders. RMRP interacts with the telomerase RT (TERT) subunit, but the influence of RMRP mutations on telomere length is unknown. We measured relative telomere length (RTL) in patients with CHH, their first-degree relatives and healthy controls and correlated RTL with clinical and laboratory features. Methods: The study cohort included 48 patients with CHH with homozygous (n=36) or compound heterozygous RMRP mutations (median age 38.2 years, range 6.0–70.8 years), 86 relatives (74 with a heterozygous RMRP mutation) and 94 unrelated healthy controls. We extracted DNA from peripheral blood, sequenced the RMRP gene and measured RTL by qPCR. Results: Compared with age-matched and sex-matched healthy controls, median RTL was significantly shorter in patients with CHH (n=40 pairs, 1.05 vs 1.21, p=0.017), but not in mutation carriers (n=48 pairs, 1.16 vs 1.10, p=0.224). RTL correlated significantly with age in RMRP mutation carriers (r=−0.482, p<0.001) and non-carriers (r=−0.498, p<0.001), but not in patients (r=−0.236, p=0.107). In particular children (<18 years) with CHH had shorter telomeres than controls (median RTL 1.12 vs 1.26, p=0.008). In patients with CHH, RTL showed no correlation with genotype, clinical or laboratory characteristics. Conclusions: Telomere length was decreased in children with CHH. We found no correlation between RTL and clinical or laboratory parameters.